Analysis of Mentoring and Coaching on Productivity Mediated by Organizational Commitment: Study Literature Review - Jaya Sakti, Reza Fauzi; Sidjabat, Sonya; Untari, Dewi; Valentin, Adelia Dwi; Rustiawan, Indra (International Journal of Advanced Multidisciplinary, 2025)
The purpose of this literature research is expected to help hypotheses for future authors in determining research related to human resource management. The research article on the analysis of mentoring and coaching on productivity mediated by organizational commitment is a scientific literature article in the scope of human resource management. The approach used in this literature review research is descriptive qualitative. Data collection techniques are using literature studies or conducting literature reviews of relevant previous articles. The data used in this study are secondary data, which are sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Mentoring affects Organizational Commitment; 2) Coaching affects Organizational Commitment; 3) Mentoring affects Productivity; 4) Coaching affects Productivity; 5) Organizational Commitment affects Productivity; 6) Mentoring affects Productivity through Organizational Commitment; and 7) Coaching affects productivity through organizational commitment.